2014
DOI: 10.1136/tobaccocontrol-2014-051648
|View full text |Cite
|
Sign up to set email alerts
|

Wanna know about vaping? Patterns of message exposure, seeking and sharing information about e-cigarettes across media platforms

Abstract: Background Awareness and use of electronic cigarettes has rapidly grown in the U.S. recently, in step with increased product marketing. Using responses to a population survey of U.S. adults, we analyzed demographic patterns of exposure to, searching for, and sharing of e-cigarette related information across media platforms. Methods An online survey of 17,522 U.S. adults was conducted in 2013. The nationally representative sample was drawn from GfK Group's KnowledgePanel® plus off-panel recruitment. Fixed eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 14 publications
8
114
1
1
Order By: Relevance
“…Research has recently appeared in which e-cigarette advertising has been examined. In this work, it has been shown that e-cigarette advertising has been widely disseminated and likely targeted at youth, with youth exposure to ecigarette advertising having increased three-fold between 2011 and 2013 (Duke et al, 2014;Emery, Vera, Huang, & Szczypka, 2014). It has also been shown that middle-school students' interest in trying alternate tobacco products (including e-cigarettes) has been influenced by tobacco advertising (Agaku & Ayo-Yusuf, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Research has recently appeared in which e-cigarette advertising has been examined. In this work, it has been shown that e-cigarette advertising has been widely disseminated and likely targeted at youth, with youth exposure to ecigarette advertising having increased three-fold between 2011 and 2013 (Duke et al, 2014;Emery, Vera, Huang, & Szczypka, 2014). It has also been shown that middle-school students' interest in trying alternate tobacco products (including e-cigarettes) has been influenced by tobacco advertising (Agaku & Ayo-Yusuf, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…3 Electronic nicotine delivery devices, commonly known as "e-cigarettes," have become increasingly popular in several countries and over the last several years, research has documented growing availability, marketing, and use of e-cigarettes in the United States. [4][5][6][7][8][9][10][11][12][13] A consistent finding from this emerging and quickly evolving area…”
Section: Introductionmentioning
confidence: 93%
“…Advertisements are filled with themes of independence and glamour, de-stigmatizing smoking and associated tobacco related products. Marketing via television, radio and billboards utilize endorsements from celebrities and have even been featured during the Super Bowl [22,23]. Television e-cigarette commercials reach an estimated population of 24 million youth, with a dramatic increase in exposure to TV ads between the years 2011 and 2013 [22].…”
Section: E-cigarettes In the Adolescent Populationmentioning
confidence: 98%